PERAN EDUKASI IBU DALAM RUMAH TANGGA - Siame, Norma Dg. (State Institute of Islamic Studies (IAIN) Palu, 2005)
Mother plays a key role at home, especially in nurturing her children. It goes without saying that early education accepted by a child comes from a mother. She has great contribution to build character of young generation. That is why Qur’anic verses and the Prophet Tradition (hadith) indicate how, without mincing words that, mother should treat her children, even early before they are born. This article tries to analyze educative role of mother at home by exploring Qur’anic verses and hadith as well as by quoting expert views. In addition, it suggests outdoor factors influencing children education. Kata Kunci: Pendidikan, Ibu, Rumah tangga